2020
DOI: 10.1021/acs.inorgchem.0c00108
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Activation of Red Phosphorus for Controlled Synthesis of Polyphosphides

Abstract: Reactions between red phosphorus (P red ) and potassium ethoxide in various organic solvents under reflux convert this rather inert form of the element to soluble polyphosphides. The activation is hypothesized to proceed via a nucleophilic attack by ethoxide on the polymeric structure of P red , leading to disproportionation of the latter, as judged from observation of P(OEt) 3 in the reaction products. A range of solvents has been probed, revealing that different polyphosphide anions (P 7 3− , P 16 2− , P 213… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…It is clearly shown from the XRD results that the pro- sphide anions. The existence of those polyphosphide clusters, especially P 16 2− , one of the most commonly reported polyphosphide anions 29,30 after RP activation, could also be affirmed via resonance signals detected in the 31 P NMR spectrum (Fig. 4f).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It is clearly shown from the XRD results that the pro- sphide anions. The existence of those polyphosphide clusters, especially P 16 2− , one of the most commonly reported polyphosphide anions 29,30 after RP activation, could also be affirmed via resonance signals detected in the 31 P NMR spectrum (Fig. 4f).…”
Section: Resultsmentioning
confidence: 64%
“…28 Thus, in order to accomplish a facile solvothermal reaction towards crystalline red phosphorus and to better understand the phase transition pathway, the selection of a mild nucleophilic solvent and appropriate reaction conditions to activate a-RP is of great significance. [29][30][31][32] Herein, we developed a solution-phase solvothermal pathway to prepare Form II red phosphorus by employing 1,2diaminopropane as a nucleophilic agent and systematically characterized the crystalline products. Crystals with high quality were obtained via optimizing the synthesis procedure, in which the reaction mechanism was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…59 It was found that the distribution of polyphosphides was highly solvent dependant, and could be expanded to affect the preparation of [P 7 ] 3− and [P 11 ] 3− polyphosphides. 60 These reactions are thought to proceed via nucleophilic attack that initiates a cascade of disproportionation reactions and rearrangements. This work was expanded to implement a topdown approach for the activation of shelf-stable P(red) using organic solvents and convenient nucleophiles in a flow-reactor to attain soluble polyphosphides on continuous multi-gram scale.…”
Section: Dalton Transactions Frontiermentioning
confidence: 99%
“…The nucleophiles that activated P(red) were expanded to include other alkoxides (KOR; where R = methyl, n-hexyl and t-butyl), thiolates (NaSR; where R = Me, Et, n-hex, i-Pr, t-Bu), and amides (KHMDS, LiHMDS, and LDA), with varying degrees of efficiency. 59,60 Hänisch and Sundermeyer found that when methylcarbonate salts were allowed to react with P(SiMe 3 ) 3 the organic salts of PCO − could be attained. However, in a similar fashion when they reacted methylcarbonate salts with Sb (SiMe 3 ) 3 , rather than SbCO − salts, XRD analysis revealed the formation of [P(nBu) 3 Me] + 3 [Sb 11 ] 3− .…”
Section: Dalton Transactions Frontiermentioning
confidence: 99%
“… 4 The isolobal relationship between the CH fragment and the P atom 5 and the diagonal relationship between carbon and phosphorus suggest a comparable reactivity for the pentaphospholide anion cyclo -P 5 − . 6 However, investigations on the reactivity of the salts of cyclo -P 5 − towards alkylhalogenides showed further aggregation to polyphosphides, 7 leaving the chemistry of pentaphospholes cyclo -P 5 R to theoretical studies for decades. 8 Similar to Cp − , cyclo -P 5 − can be stabilized within the coordination sphere of different TMs 9 and is thus closely associated with the TM-mediated conversion of P 4 .…”
Section: Introductionmentioning
confidence: 99%